ON INEXACT TIKHONOV AND PROXIMAL POINT REGULARISATION METHODS FOR PSEUDOMONOTONE EQUILIBRIUM PROBLEMS - Phạm Gia Hưng; Lê Dũng Mưu (Tạp chí Khoa học Đại học Đà Lạt)
We investigate the inexact Tikhonov and proximal point regularisation methods for pseudomonotone equilibrium problems. In this ease, the regularised sub-problems may be not strongly monotone, even not pseudomonotone. However, any iterative sequence of the regularised sub-problems tends to the same solution of the original problem which is nearest to the starting point for the Tikhonov method.